METTL3 Induces AAA Development and Progression by Modulating N6-Methyladenosine-Dependent Primary miR34a Processing - Lintao Zhong; Xiang He; Haoyu Song; Yili Sun; Guojun Chen; Xiaoyun Si; Jie Sun; Xiaoqiang Chen; Wangjun Liao; Yulin Liao; Jianping Bin (Elsevier, 2020)
Identifying effective drugs to delay the progression of aortic aneurysms is a formidable challenge in vascular medicine. Methyltransferase-like 3 (METTL3) plays a key role in catalyzing the formation of N6-methyladenosine (m6A), but despite the functional importance of METTL3 and m6A in various fundamental biological processes, their roles in abdominal aortic aneurysm (AAA) are unknown. Here, we found that METTL3 knockdown in apolipoprotein E-deficient (ApoE−/−) mice treated with angiotensin II suppressed the formation of AAAs, while METTL3 overexpression exerted the opposite effects. Similar results were obtained in a calcium chloride (CaCl2)-induced mouse AAA model. Mechanistically, METTL3-dependent m6A methylation promoted primary microRNA-34a (miR-34a, pri-miR34a) maturation through DGCR8. Moreover, miR-34a overexpression significantly decreased SIRT1 expression and aggravated AAA formation, while miR-34a deficiency produced the opposite effects. In a rescue experiment, miR-34a knockdown or forced expression of SIRT1 partially attenuated the protective effects of METTL3 deficiency against AAA formation. Our studies reveal an important role for METTL3/m6A-mediated miR-34a maturation in AAA formation and provide a novel therapeutic target and diagnostic biomarker for AAA treatment.